Study of the cladodes phenotypic diversity of 36 accessions of cactus in the arid region of Tafilalet - Homrani Bakali A.; Noutfia Y.; Ibnelbachyr M.; Ichir L.L.; Alem C.; Boujghagh M. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The prickly pear (Opuntia ficus indica Mill.) could be one of the most important forage crop species in the arid southeast region of Morocco. In this work, we report the analysis of cladodes traits belonging to 36 accessions of prickly pear (28 accessions of Opuntia ficus indica form inermis and 8 accessions of Opuntia ficus indica form amycleae) from different regions of Morocco and grown in the experimental station of Errachidia. Twenty-three phenotypic characters of cladodes were analyzed using analysis of variance and multivariate analysis (PCA). All attributes were significantly different within and between the two forms of cacti. The shape of the cactus and the geographical origin affected the characteristics of the cladodes. Comparison of our results with those obtained for the same accessions grown in the station Melk Zehar located in Agadir (southwest Morocco) revealed significant differences in favor of the Agadir environment. This study allowed us to group the characters of the cladodes into three classes for the two cactus forms.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)